Serum Immunoglobulins Levels in Autoimmune Hepatitis of Iraqi Patients - AL- Obeidy, Eman Sh.; Abbs, Nahida R.; Al-Naim, Samira N.; Najeeb, Akram A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Autoimmune hepatitis (AIH) is an unresolving inflammation of the liver of unknown cause associated with interface hepatitis on histological examination,hypergammaglobulinemia and presence of circulating autoantibodies. Antibody-mediated tissue injury might be responsible for tissue injury in AIH therefore; a number of studies have been focused on the immunoglobulines in these patients .The aim of the study is to estimate the level of immunoglobulins (IgG, IgA and IgM ) in different types of Autoimmune hepatitis ( AIH). Patients and Methods: The study was performed on 73 Iraqi patients with autoimmune hepatitis (AIH), attending the teaching hospital for gastroenterology and liver disease in a period between November 2003 and July 2004. : Anti- soluble liver ANA, SMA, LKM-1, and LC-1 Abs were detected using Enzyme-Linked Immunosorbent Assay (ELISA) technique. Anti-SLA/LP was detected using the Euroline method.Quantitation of serum IgG, IgA and IgM of the study groups were carried by single radial immudiffusion (SRID) test. Equal volume Results: Significant differences was observed between AIH patients and healthy control group in the mean level of IgG ,IgA and IgM. In addition, level of IgA in the sera of patients with type 2 was lower than those of type 1 and 3. Conclusion: It was conclude that in patients with AIH, the Immunoglobulin G was significantly higher in type-1, whereas IgA was significantly lower in AIH-2 patients compared to other types of the disease.